Pengaruh Penambahan Tepung Rumput Laut (sargassum sp.) Pada Pakan Terhadap Pertumbuhan dan Sintasan Benih Ikan Nila (oreochromis niloticus) - Ahriani, Andi Fifi; Syam, Husain; Patang (Jurnal Pendidikan Teknologi Pertanian, 2023)
Feed in the cultivation of tilapia seeds greatly affects the results of cultivation. The purpose of this study was to determine the effect of adding Sargassum sp. brown seaweed flour. on feed to the value of the food conversion ratio (FCR) of feed on tilapia fry. and Knowing the concentration of addition of Sargassum sp. on the growth and survival of tilapia fry. This study used the ANOVA test to compare the treatment with feeding with the addition of Sargassum sp. different in feed. The dose of feeding is 5% of the weight of the fish for 30 days of maintenance with the frequency of feeding 3 times a day. Parameters observed were weight gain, length, FCR (food conversion ratio) survival and water quality parameters, namely temperature, pH, DO, and ammonia. The results showed that treatment C was the best treatment, namely feed with the addition of Sargassum sp flour. 60g/1kg commercial feed. The highest C treatment experienced better growth and water quality